PROFIL TOKOH PEREMPUAN DALAM KABA RAMBUN PAMENAN KARYA SUTAN MANGKUDUN - Ninawati Syahrul (SAWERIGADING, 2010)
Kaba is the legend of Minangkabau people as a folklore. It is a great literature in Minang and has an important role in Minangkabau society. Minang’s literature is dominant to show women’s profile. There is a relation with the kinship system which is adhered by the community. It puts matrilineal system which studied the existence of women’s profile. So, it is interesting to be examined. This research is descriptive study. It aims to describe  women’s profile in Kaba Anggun Nan Tungga especially in Minangkabau society system. This study uses the literature objective approach  related to female psychology theory, common psychology, and human philosophy. The women’s profile which is described in Kaba Rambun Pamenan shows that women’s figure personality generally determined and wise to face suffering in their life. They also a glorious aims to reach an ideal life.   Abstrak Karya sastra daerah Minangkabau cukup dominan menghadirkan tokoh perempuan. Bila dihubungkan dengan sistem kekerabatan yang dianut masyarakatnya, yakni matrilineal, maka sangat menarik untuk dikaji mengenai eksistensi tokoh perempuan. Penelitian ini bertujuan mendeskripsikan profil tokoh perempuan dalam Kaba Anggun Nan Tungga  terutama kepribadiannya dalam kehidupan Minangkabau. Penelitian ini bersifat deskriptif. Untuk melihat gambaran profil perempuan dalam penelitian ini digunakan pendekatan objektif sastra yang dikaitkan dengan teori psikologi perempuan, psikologi umum, dan filsafat manusia. Profil tokoh perempuan yang digambarkan dalam Kaba Rambun Pamenan menunjukkan bahwa kepribadian tokoh perempuan pada umumnya tabah, cenderung arif menghadapi penderitaan hidup dan mempunyai cita-cita yang luhur untuk menuju kehidupan yang ideal.